SYMPATISK ETNOGRAFI ELLER SOLIDARISK KRITIK? - Johansen, Louise Victoria (Tidsskriftet Antropologi, 2002)
Traditionally, anthropologists have sympathized with marginalized objects of study – people who do not have the power to speak for themselves. Acting as advocates of subordinate groups has thus seemed much more attractive to anthropologists than studying institutions and powerful informants. Though many recent studies of Western institutions and elite groups have modified this viewpoint, a marked tendency still exists to criticise these informants for being unambiguously hegemonic, whereas minorities are almost automatically rendered as complex. The article considers the methodological implications of letting the status of the informants influence which ethical codex is to be followed – a sympathetic approach to marginalized people, or a critical approach to dominant groups and institutions. It is argued that fieldwork among elites can hardly be legitimized if it does not strive to render their worlds more comprehensible and varied. Exemplified trhough a recent study of the relations between teachers and bilingual pupils in two French primary schools, it is shown that the French teachers’ multiple discourses on differences among the children cut across the so-called “dominant” discourse normally addressed by educational and minority anthropology. This article shows that a focus on the complexity of institutions and powerful elites can point to possibilities within the field studied for enhancing equality. A more solidary perspective should therefore inspire critical anthropology to break with the usual dichotomy between power or elite and the “victims” hereof. Instead, we need to engage all parties studied as competent and often reliable informants in order to make our critique more accurate.